Literarni liki v kratkih zgodbah Andreja Blatnika - Pavlič, Darja (Primerjalna književnost, 2020)
Andrej Blatnik's short stories are based not on the actions of literary characters, but on their consciousness, which is foregrounded. Therefore, appropriate tools for their analysis are concepts that have evolved within the framework of cognitive narratology. In the article, I specifically highlight the notion of experientiality introduced by Monika Fludernik to explain narrativity. Due to its complexity, I seek to explain the concept by pointing to its connection with readers, literary characters, and storytellers. At the level of literary characters, experientiality can be equated with their consciousness, especially when consciousness is understood in relation to the body or as an embodied mind. Blatnik's literary characters respond emotionally and physically to events, reflect on their never-realized plans, and often ponder how others see them. As a rule, they are unsuccessful in reading the minds of other characters, which I show by analyzing three selected short stories: the postmodernist "Story about Rošlin and Verjanko", the minimalist "Wet Walls", and the modernist "Out of Passion".
Keywords: Blatnik, Andrej; cognitive narratology; consciousness; experientiality; Fludernik, Monika; izkustvenost; kognitivna naratologija; kratka zgodba; literarni liki; literary characters; narrative structure; pripovedna struktura; short story; Slovenian literature; slovenska književnost; zavest